The Tasmanian Estuary Perch Population—A Threatened Species? - Jonah L. Yick; Bryan Van Wyk; James Haddy (Fishes)
Estuary perch (Percalates colonorum) are a long-lived and slow-growing species which are distributed throughout southeastern Australian estuaries. In Tasmania, only one known population remains which is located in the Arthur River, on the remote northwest coast. Tasmania is the only Australian state to list estuary perch as a wholly protected species (recreational and commercial), while other populations across their mainland distribution appear to be robust. A survey undertaken on estuary perch in the Arthur River in 2014–2015 indicated that the population was small (825–2375 fish) and dominated by three age classes between 12 and 14 years old. This population also has extremely low genetic diversity and is genetically distinct to mainland populations due to its geographic isolation. During a re-survey in December 2023, 378 estuary perch were captured, with 191 tagged and released, and 31 fish retained for age and gonad analysis. Although three strong age classes were detected (five, eight and twenty-three years), numerous weak and missing cohorts were apparent. This study also confirms this population has a delayed spawning season in comparison to mainland populations, with growth models and tag recaptures (32 fish) demonstrating a very slow but sexually dimorphic growth rate. By combining the datasets of the 2014/15 and 2023 survey, we present an updated understanding of the biology and population dynamics of this unique Tasmanian population, which has previously never been published. The results confirm the population is still reproductively active and stable; however, due to their restricted distribution, variable recruitment, slow growth, and small population, further conservation efforts are still required. Further legislative listings at both the state and federal levels are planned, which if successful will provide additional protection and assist in applications for external funding and resources. This will support the development of a recovery plan which will consider re-stocking efforts and re-establishment of previously inhabited waters and investigate potential actions to improve the genetics of the Tasmanian population. Additionally, educational campaigns to inform the public and recreational fishers on the status of estuary perch in Tasmania will be undertaken.